Responsive Management of Islamic Education to Local Linguistics: Challenges and Innovations in School Management Practices (Case Study in Gorontalo Regency) - Toino, Elma; Pateda, Lamsike; Hula, Ibnu Rawandhy N.; Mariana, Ana; Pakaya, Nurul Aini N. (ELOQUENCE : Journal of Foreign Language, 2023)
Background: Islamic education in Gorontalo Regency operates within a rich multilingual context, yet it remains insufficiently responsive to local linguistic resources, particularly the Gorontalo language. Although the local language holds significant potential to enhance students’ understanding of Islamic values and engagement, its integration into school management is hindered by a lack of formal policies, academic stigma, and limited supporting resources. Purpose: This study aims to examine how Islamic education management responds to local linguistic contexts and formulate an integrative management model that harmonizes Islamic values with local language practices. Method: Employing a qualitative-descriptive approach with a constructivist design, the research was conducted in Gorontalo Regency through in-depth interviews, participant observation, and document analysis. Data were collected from 20 informants, including madrasah principals, teachers, Ministry of Religious Affairs officials, and customary leaders. Results and Discussion: Findings reveal that 92% of respondents recognize the importance of the Gorontalo language, only 46% of institutions have implemented it in formal policies, and only 27% of teachers have received relevant training. The local language proves effective in teaching moral character (76%) and religious communication (82%), yet faces structural barriers such as the absence of regulatory support, academic marginalization of local languages, and a scarcity of bilingual teaching materials. Support from customary and religious leaders significantly strengthens cultural legitimacy. Moreover, using the local language demonstrably enhances student participation, comprehension of Islamic values, and religious behavior. Conclusions and Implications: Synthesizing empirical findings with theoretical frameworks—Funds of Knowledge, sociolinguistics, Contextual Teaching and Learning, and Fazlur Rahman’s thought—this study proposes a conceptual model: “Locally Linguistically Responsive Islamic Education Management.” The model comprises four pillars: institutional policy, contextual learning management, culturally grounded teacher capacity building, and socio-religious collaboration. It bridges the universality of Islamic values with local cultural specificity, contributing to both the preservation of indigenous languages and the contextual strengthening of Islamic identity. The study recommends that Islamic education adopt inclusive, context-sensitive management approaches to foster meaningful and sustainable learning.